Histopathological Observation of The Qurban Goat’s (Capra Aegagrus Hircus) Lung Organs in Tulus Rejo Village, Pekalongan District, East Lampung 2019 Suspected Of Being Infected With Pneumonia - Alqoriani A, Ostarica; Busman, Hendri; Susanto, Gregorius Nugroho; Nurcahyani, Nuning; Arofah, Nur Lailatul (IJIS Edu : Indonesian Journal of Integrated Science Education, 2020)
Placement of goats of various ages and the number of animals that exceed the maximum limit in one cage can cause the spread of diseases caused by viruses, bacteria, etc. One of them can cause pneumonia. Dirt and extreme temperatures in East Lampung are feared to increase the growth of bacteria that cause pneumonia. The purpose of this research was to determine the type of pneumonia that infects and the differences between the histopathological organs of the healthy qurban goats and those infected with pneumonia. This research was conducted in October-November 2019 at the Pathology Laboratory of the Veterinary Institute of Lampung. About 13 samples of lung organ of goat qurban (Capra aegagrus hircus) were taken from the Baburahman mosque of Tulus Rejo Village, Pekalongan District, East Lampung. The results of the study found 6 samples of positive qurban goat lungs infected with pneumonia, with the characteristics of inflammatory cells accompanied by thickening of the septa alveoli, edema, and the presence of hemorrhage. Based on observations, the most infecting types of pneumonia are pulmonary edema and peri-bronchial edema